Stand-alone posterior ressection of lumbar hemivertebrae: Case report - Rodrigues, Luciano M. R.; Yonezaki, Adriano M.; Ueno, Fabrício H.; Valesin, Edgar S.; de Abreu, Luiz Carlos; Valenti, Vitor E. [UNESP]; Foizer, Guilherme A.; Milani, Carlo (My University, 2012)
Background: In this case report we presented the stand-alone posterior approach for hemivertebra resection with unilateral laminar hooks. Case report: The patient was male and five years old. The coronal and sagital X-Rays images showed a failure of vertebral formation, segmented hemivertebra of third lumbar vertebra. The segmented hemivertebra caused a thoracolumbar scoliosis from T12 to L4 (rightside convexity), of 30 degrees (Cobb angle). The patient was submitted to a hemivertebra resection from posterior approach with two unilateral laminars hooks stabilization (superior lamina in L2 and inferior lamina of L4) in association to a compression system and autologus bone graft. The coronal X-Ray image after surgery showed a partial improvement to 25 degrees (Cobb angle) between L2 and L4. After three years of follow up it was not observed system failure (hook pull-out), maintance of curve (25 degrees of Cobb angle) and correction of trunk inbalance. Conclusion: The hemivertebra resection with posterior approach is safe, with satisfactory correction of scoliosis curve, which means is a good choice for congenital scoliosis surgical treatment.
Keywords: Congenital malformations; Hemivertebrae; Scoliosis